Tuning the flow of light in two-dimensional metallic photonic crystals based on Faraday effect. Issue 1 (2nd January 2017) - Aly, Arafa H.; Elsayed, Hussein A.; El-Naggar, Sahar A.
Abstract: In this paper, we investigate the tunability of two-dimensional metallic photonic crystals by an external magnetic field. Our theoretical analysis is based on the frequency-dependent plane wave expansion method. The numerical results show that the external magnetic field has a pronounced effect on the permittivity of the metals. Therefore, the photonic band structures can be strongly tuned and controlled by adjusting the external magnetic field. Our structure is a good candidate for many applications such as filters, optical switches and modulators.